Indonesian Islamic Law Review on the Marriage Customs of Juelen and Angkap in Gayo Tribes, Central Aceh District - Mulyadi Mulyadi; Asmuni Asmuni; Sukiman Sukiman (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
This study presents the latest information on a review of Islamic law towards marriage customs of juelen and angkap in Gayo tribe, Central Aceh District. This research uses the theory of mashlahah: the applicative theory is used in analyzing the research data and in the end of the research shows that the effect of marriage custom of Gayo on juelen and angkap must continue to give part to each party (ex-husband and wife) especially the marriage of Angkap, and if there is a dowry debt as in marriage of angkap, then it can be settled after sharing of shared assets between the former wife and husband. This awarding is based on consideration of mercy on the basis of providing guarantees in life after the divorce occurred.  Obviously by giving a share to the husband or wife of shared assets as a result of the marriage customs of juelen / angkap in Gayo custom, it is still based on the idea behind the spirit of KHI that seeks to translate shared assets as a means to guarantee life after divorce and of course this is in line with the legal basis Islam. Thus, the formulation of article 85-97 KHI is considered to fulfill the values of benefit in maintaining humanitarian relations and the benefit of family.